Into the deep: a quantitative analysis of teacher ratings of the development and implementation of a trial religious education curriculum - Sultmann, William (British Journal of religious education, 2022)
The Scriptural metaphor, ‘Into the Deep’, characterises a trial Religious Education curriculum within a Catholic diocese of Australia. Teacher developers (n = 40) and teacher implementers (n = 85) from 37 schools responded to the influence of six Religious Education Development Principles (REDP), and statements on the implementation processes at school and across the diocese. Responses to the REDP achieved a high and consistent overall mean rating of 4.25 on a 5-point Likert scale and a mean of 3.97 for resourcing and strategic implementation processes. Least confidence was reported for development principles of Experiential Learning and Learning Through Integration. Implementation processes favoured resourcing and strategic support at the school level. Overall, responses of teacher developers, in comparison to teacher implementers, were statistically significant, with ratings improving with years of teacher experience and from primary school personnel. Implications of findings were that early career teachers and teachers across school types, other than primary, should be prioritised for support.